The study on entrepreneurship program among the students of Bachelor in Accountancy UiTM Jengka, Pahang / Munirah Azmi - Azmi, Munirah (2013)
The research entitled "The Study of Student Entrepreneurship Program among The Students of Bachelor in Accountancy UiTM Jengka, Pahang". There are two objectives highlighted in this study which are to analyze the entrepreneurial intentions of Bachelor in Accountancy students in UiTM, Jengka, Pahang and to determine the perception about entrepreneurship program among Bachelor in Accountancy students in UiTM, Jengka, Pahang. The scope of the study was concentrated on intention of entrepreneurship program among Bachelor in Accountancy students from semester four until semester eight. The researcher used descriptive research as research design and the sampling technique is stratified sampling technique. This study more focused to students from Bachelor in Accountancy students and 92 respondents was selected to fulfill and completed the questionnaires. At the end of the findings several recommendations have been made for the organization and also for future research purpose.